2021
DOI: 10.3389/fgene.2021.627055
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Approaches Reveal Pleiotropic Effects in Crossbred Beef Cattle

Abstract: Carcass and meat quality are two important attributes for the beef industry because they drive profitability and consumer demand. These traits are of even greater importance in crossbred cattle used in subtropical and tropical regions for their superior adaptability because they tend to underperform compared to their purebred counterparts. Many of these traits are challenging and expensive to measure and unavailable until late in life or after the animal is harvested, hence unrealistic to improve through tradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…Animals in this herd are raised as contemporaries and range from 0% to 100% Bos Taurus Indicus influence. Many economically important traits have been studied in this population to determine the optimum Brahman genetics composition producers interested in improving the thermotolerance in their herds while maximizing production traits ( Elzo and Wakeman, 1998 ; Elzo et al, 2012 ; Elzo et al, 2016 ; Dikmen et al, 2018 ; Rezende et al, 2021 ; Martins et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Animals in this herd are raised as contemporaries and range from 0% to 100% Bos Taurus Indicus influence. Many economically important traits have been studied in this population to determine the optimum Brahman genetics composition producers interested in improving the thermotolerance in their herds while maximizing production traits ( Elzo and Wakeman, 1998 ; Elzo et al, 2012 ; Elzo et al, 2016 ; Dikmen et al, 2018 ; Rezende et al, 2021 ; Martins et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Those nine genes are located on BTA 4, 14, and 18. The region on BTA 4 has been reported for mastitis resistance ( Rupp and Boichard, 2003 ), growth ( Lu et al, 2013 ), fertility ( Grigoletto et al, 2020b ), and primarly milk ( Ibeagha-Awemu et al, 2016 ; Sanchez et al, 2017 , 2019 ; Van Den Berg et al, 2020 ), while the region on BTA 14 was primarly reported for meat ( Bolormaa et al, 2011 ; Neto et al, 2012 ; Saatchi et al, 2014 ; Sharma et al, 2014 ; Ali et al, 2015 ; Song et al, 2016 ; Kim et al, 2017 ; Akanno et al, 2018 ; Grigoletto et al, 2020a ; Srikanth et al, 2020 ; Wang et al, 2020 ; Rezende et al, 2021 ), production ( Snelling et al, 2010 ; Lu et al, 2013 ; Martínez et al, 2014 ; Saatchi et al, 2014 ; Akanno et al, 2018 ; Zhong et al, 2019 ; Zhang et al, 2020 ), and exterior traits ( Pryce et al, 2011 ; Pausch et al, 2016 ; Wu et al, 2016 ; Marete A. G. et al, 2018 ; Bouwman et al, 2018 ; Tribout et al, 2020 ). Within this region, for example, we find the gene XKR4 associated with subcutaneous rump fat thickness and growth ( Neto et al, 2012 ; Magalhã et al, 2016 ; An et al, 2019 ; Smith et al, 2019 ) .…”
Section: Discussionmentioning
confidence: 99%
“…These findings support farmers’ perceptions about the good tolerance of Noticiana to summertime heat. Additionally, STAT6 and GPR182 are potential meat quality genes in livestock species ( 74 ). Noticiana shared with Comisana ( 58 ), and Barbaresca ( 75 ) the hotspot in OAR6:35.70–39.80 which is a region fairly fixed in sheep species ( 69 , 76 ), particularly in European breeds ( 77 – 79 ).…”
Section: Discussionmentioning
confidence: 99%